Concentrated solar radiation enhanced one pot synthesis of DES and N-Phenyl phthalimide - Ghorpade, P.; Gadilohar, B.; Pinjari, D.; Shinde, Yogesh; Shankarling, G. (2015)
© 2015 Elsevier Ltd. A simple, rapid and energy efficient process has been developed for the synthesis of ChCl-Urea based Deep Eutectic Solvents (DES) using concentrated solar radiations (CSR). The DES thus synthesized has been successfully used for the synthesis of N-Phenyl phthalimide from aniline and phthalic anhydride under CSR. The use of CSR greatly influenced on reaction rate as reaction proceeded in fifteen minutes. The product formed by CSR method were evaluated using TGA, XRD, and microscopic study and were found to be comparable with that obtained by conventional heating method. The present protocol covers various principles of green chemistry as it utilizes greener and clean source of energy, time saving and energy efficient process (almost 91% of energy can be saved).